A patenting perspective on human neutrophil elastase (HNE) inhibitors (2014-2018) and their therapeutic applications. (3rd July 2019) - Crocetti, L; Quinn, MT; Schepetkin, IA; Giovannoni, MP
ABSTRACT: Introduction : Human neutrophil elastase (HNE) is involved in a variety of serious chronic diseases, especially cardiopulmonary pathologies. For this reason, the regulation of HNE activity represents a promising therapeutic approach, which is evident by the development of a number of new and selective HNE inhibitors, both in the academic and pharmaceutical environments. Areas covered : The present review analyzes and summarizes the patent literature regarding human neutrophil elastase inhibitors for the treatment of cardiopulmonary diseases over 2014–2018. Expert opinion : HNE is an interesting and defined target to treat various inflammatory diseases, including a number of cardiopulmonary pathologies. The research in this field is quite active, and a number of HNE inhibitors are currently in various stages of clinical development. In addition, new opportunities for HNE inhibitor development stem from recent studies demonstrating the involvement of HNE in many other inflammatory pathologies, including rheumatoid arthritis, inflammatory bowel disease, skin diseases, and cancer. Furthermore, the development of dual HNE/proteinase 3 inhibitors is being pursued as an innovative approach for the treatment of neutrophilic inflammatory diseases. Thus, these new developments will likely stimulate new and increased interest in this important therapeutic target and for the development of novel and selective HNE inhibitors.